FROM THE NATIONAL COUNCIL FOR COMBATING DISCRIMINATION TO THE COURT OF JUSTICE OF EUROPEAN UNION – CASE C-81/12 - CRISTIAN JURA (Challenges of the Knowledge Society)
The scope of this research is to present and analyze national and European, jurisdictional-administrative procedural issues, if courts are notified related to certain discriminatory statements. The starting point of the research consists in some statements made during a radio show. During the research, the following are analyzed: notification of the National Council for Combating Discrimination (CNCD), decision of the National Council for Combating Discrimination, challenge of the resolution of the National Council for Combating Discrimination at the Court of Appeal Bucharest, notification of the Court of Justice of European Union by the Court of Appeal Bucharest and the beginning of the procedures before the Court of Justice of the European Union. The scientific demarche has as objectives a better understanding of the mechanisms of operation of every institution involved in this process, as well as the chronology of the terms necessary to settle this case.